“Caracterização preliminar da qualidade das águas subterrâneas do projeto Assentamento Gamaliel, Cuiabá-MT” - Gomes, Isael Minson (2016)
The Projeto Assentamento Gamaliel (PAG) comprises an area of approximately 2.46 km2 , located in the countryside of the city of Cuiabá, near the Glory Altos district. In 2008, 175 families were settled on plots of 1.2 ha, where public water supply is made only by wells. The urban population growth progresses toward the settlement and can bring in the near future impacts on the quality and quantity of groundwater in the PAG. Given this situation, this study had the main objective to perform a hydrochemical study of groundwater from field surveys and laboratory, featuring physical and chemical properties of groundwater resources in the locality. The samples were collected and analyzed between May and June 2015, and following analysis methodology of the Standard Methods for the Examination of Water and Wastwater (2012) was determined calcium, potassium, sodium, magnesium and iron by optical spectrometry atomic emission inductively coupled plasma (ICP-OES), chloride, nitrate and sulfate by ionic chromatography (IC), total alkalinity by titration, and pH, electrical conductivity and temperature measured in multiparameter probe. The data were statistically analyzed with the help of IBM® SPSS Statistics program v. 24.0 and hydrochemical analysis with the help of Qualigraf® program v. 1.17. The results showed chemically similar waters, with seven samples classified as magnesian bicarbonate waters and as calcium bicarbonate, hypothermal, neutral to alkaline, with an average calcium and magnesium content, which reflects the geology of the Cuiabá Group and is also free of iron, despite the occurrence of pyrites in the region. They are of good quality for human consumption, agriculture and livestock.